2005
DOI: 10.1016/j.neuropsychologia.2004.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Visual memory loss and autobiographical amnesia: a case study

Abstract: Amnesia typically results from trauma to the medial temporal regions that coordinate activation among the disparate areas of cortex that represent the information that make up autobiographical memories. We proposed that amnesia should also result from damage to these regions, particularly regions that subserve long-term visual memory [Rubin, D. C., & Greenberg, D. L. (1998). Visual memory-deficit amnesia: A distinct amnesic presentation and etiology. Proceedings of the National Academy of Sciences of the USA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 74 publications
7
62
0
Order By: Relevance
“…Although medial temporal damage might account for some of the memory loss in some of these cases (5 of the 11 patients had some sign of medial temporal damage), the patterns of the deficits suggest otherwise. In-depth testing of 1 of these 1 1 patients confirmed our general observations (Greenberg, Eacott, Brechin, & Rubin, 2005). The findings are consistent with most neuropsychological and neural net theories of memories (e.g., McClelland et al, 1995;Schmajuk & DiCarlo, 1992), and aspects of our explanation of visual memory deficit amnesia were considered in 2 of the case studies we reviewed (Hunkin et al, 1995;Ogden, 1993).…”
Section: Neuropsychologysupporting
confidence: 84%
“…Although medial temporal damage might account for some of the memory loss in some of these cases (5 of the 11 patients had some sign of medial temporal damage), the patterns of the deficits suggest otherwise. In-depth testing of 1 of these 1 1 patients confirmed our general observations (Greenberg, Eacott, Brechin, & Rubin, 2005). The findings are consistent with most neuropsychological and neural net theories of memories (e.g., McClelland et al, 1995;Schmajuk & DiCarlo, 1992), and aspects of our explanation of visual memory deficit amnesia were considered in 2 of the case studies we reviewed (Hunkin et al, 1995;Ogden, 1993).…”
Section: Neuropsychologysupporting
confidence: 84%
“…The importance of MVI in AbM is supported both by case reports of autobiographical amnesic patients presenting, primarily, an MVI deficit (Greenberg, Eacott, Brechin, & Rubin, 2005;Rubin & Greenberg, 1998), and neuroimaging studies showing that imagination of fictitious scenes and AbM are sustained by overlapping cerebral network activations (Hassabis, Kumaran, & Maguire, 2007;Huijbers et al, 2011). On this basis, the use of MVI in the context of the present study was promising, all the more so that MVI had already been used as a rehabilitation technique in MS (Chiaravalloti et al, 2005).…”
Section: Introductionsupporting
confidence: 62%
“…Several lines of research have shed light on this question, but they have not yet yielded a definitive answer. As we noted earlier, people who lose visual imagery because of a neurological injury tend to have severe retrograde amnesia; their anterograde memory tends to be better, although the data are quite meager, and we do not know why these memories are not as severely affected (Greenberg et al, 2005;O'Connor et al, 1992;Ogden, 1993). Although these cases suggest that visual imagery plays a vital role in autobiographical memory, they only tell part of the story.…”
Section: Abstract Autobiographical Memory Imagerymentioning
confidence: 74%
“…Neuropsychological studies have revealed that people with an acquired imagery deficit often have profound autobiographical amnesia (Greenberg, Eacott, Brechin, & Rubin, 2005;O'Connor, Butters, Miliotis, Eslinger, & Cermak, 1992;Ogden, 1993). Neuroimaging studies have demonstrated that autobiographical retrieval is associated with increased activation in posterior cortical regions that play a role in visual imagery (for reviews, see Cabeza & St. Jacques, 2007;Spreng, Mar, & Kim, 2009;Svoboda, McKinnon, & Levine, 2006).…”
Section: Abstract Autobiographical Memory Imagerymentioning
confidence: 99%